Law on Judicial Expertise - The Nationnal Assembly (2012)
This Law provides for judicial experts; judicial expertise institutio ns; ad hoc judicial expertise performer, ad hoc judicial expertise institutions; judicial expertise activities; judicial expertise charge, regulations and policies applicable to judicial expertise activities, and responsibilities of state agencies to judicial expertise institutions and activities.